ENERGY EFFICIENT DISTILLATION COLUMNS ANALYSIS FOR AN AROMATIC SEPARATION PROCESS (Jurnal Teknologi (Sciences & Engineering), 2016)
Energy savings is a major challenge in distillation operations. However, there is still one problem, which is how do we improve the energy efficiency of the existing distillation column systems without major modifications. Recently, a new energy efficient distillation columns methodology that will be able to improve energy efficiency of the existing separation systems without having major modifications has been developed. Therefore, the objective of this paper is to present a new improvement of the existing methodology by designing an optimal sequence of energy efficient distillation columns using a driving force method. Accordingly, the methodology is divided into four hierarchical sequential stages: i) existing sequence energy analysis, ii) optimal sequence determination, iii) optimal sequence energy analysis, and iv) energy comparison and economic analysis. The capability of this methodology is tested in designing an optimal synthesis of energy efficient distillation columns sequence of an aromatics separation unit. The existing aromatics separation unit consists of six compounds (Methylcyclopentane (MCP), Benzene, Methylcyclohexane (MCH), Toluene, m-Xylene and o-Xylene) with five direct sequence distillation columns being simulated using a simple and reliable short-cut method and rigorously tested within an Aspen HYSYSÂ® simulation environment. The energy and economic analyses show that the optimal sequence determined by the driving force method has a better energy reduction with a total of 6.78% energy savings and a return of investment of 3.10 with a payback period of 4 months. It can be concluded that, the sequence determined by the driving force method is not only capable in reducing energy consumption, but also has a better economic cost for an aromatic separation unit